The major principles of evaluating total value and competitiveness of services - Žvirblis, Algis (Business: Theory and Practice, 2007)
Major features of specific services have much in common with other services, being, however, more closely related to marketing strategies. The article deals with the principles of quantitative evaluation of competitiveness of  services. The complex approach to the above problems should be developed. The major goal of the present investigation is to develop basic theoretical principles for the analysis of total value and competitiveness of  services and  competitive advantage of service companies aimed at solving actual problems. Let us consider, for example, basic principles of evaluation of the competitiveness of road transport services. For this purpose, a new concept referred to as the total value of the transport services is offered. It reflects more detailed evaluation of services quality. For a general case, the model for the services value may be expressed as the dependence of  total value vector on the vectors of local values. The index of competitiveness may be expressed in terms of the concept of total value. In determining the impact of inside factors on the performance of the services system, the emphasis should be placed on competitive advantage as a major criterion reflecting its effectiveness. The goal is to establish the relationship between them and the efficiency characteristics of the above system, as well as its competitive advantage. In the present investigation, the suggested evaluation criteria imply that competitiveness (competitive advantage) of the services system is expressed in terms of the vector belonging to a set of vectors generally describing how effectively the system performs. Competitiveness is, in turn, defined by a  system of inside components: marketing management and technological competitiveness, competitiveness of services and level of diversification (differentiation).Article in Lithuanian.Paslaugų bendrojo vertingumo ir jų konkurencingumo vertinimo principaiSantrauka. Nagrinėjama paslaugų apskritai ir specifinių paslaugų, pvz., vežimų kelių transportu, konkurencingumo vertinimo problematika. Pagrindinis dėmesys skirtas teoriniam tyrimui, kurio tikslas - pirmiausia pasiūlyti paslaugos bendrojo vertingumo kaip kompleksinio paslaugos kokybės, t. y. visuminės jos vertės, mato vertinimo principus bei modelius. Sukurtas paslaugos vertingumo modelis bendru pavidalu išreikštas vektoriumi, kurį apibrėžia atskirų paslaugos kokybės ir kitų įtakos veiksnių subvektorių matrica. Tokiu būdu pereinama prie formalizuotos paslaugos konkurencingumo išraiškos (iš principo remiantis bendruoju konkurencingumo indeksu). Taip pat pateikti paslaugą teikiančios įmonės konkurencingumo (jos konkurencinio pranašumo) vertinimo principai: tai siūloma atlikti remiantis kompleksinių paslaugos teikimo sistemos (įskaitant marketingo sistemą) komponentų sinteze. Išskirti šie kompleksiniai komponentai: vadybinis konkurencingumas, technologinis konkurencingumas ir paslaugos konkurencingumas. Teikiant skirtingas paslaugas tikslinėse rinkose, turi būti įtraukiamas papildomas diversifikacijos lygio (diferenciacijos) komponentas.Reikšminiai žodžiai: specifinė paslauga, vertingumas, konkurencingumas, konkurencinis pranašumas, veiksniai, kompleksiniai komponentai, diversifikacijos lygis, diferenciacija, komponentų sistema.